Thermal radical initiator derivatives based on O‐imino‐isourea: Synthesis, polymerization, and characterization. Issue 22 (10th August 2016) - Kim, Beomjin; Lee, Dong Geun; Kim, Dong Yeon; Kim, Hyeok Jin; Kong, Nam Sik; Kim, Jin Chul; Noh, Seung Man; Jung, Hyun Wook; Park, Young IL
ABSTRACT: The new thermal radical initiators (TRIs) with linear and cyclic type groups based on derivatives of O ‐imino‐isourea have been designed and synthesized. The radical polymerization property of the synthesized TRI derivatives as a radical initiator in n‐butyl acrylate was monitored by differential scanning calorimetry analysis. TRI derivatives with linear type groups, such as 3‐PenDCC, 3‐HexDCC, and 4‐HepDCC, showed peak temperatures ( T peak ) of 80–84 °C, whereas those with cyclic type groups, such as C‐PenDCC, C‐HexDCC, and C‐HepDCC, exhibited a wide T peak distribution in the 74–87 °C range. The polymerization efficiency using new TRIs in n ‐butyl acrylate was elaborately identified from the molecular weights and conversion obtained using gel permeation chromatography analysis and NMR spectroscopy. To consider their possible application to automotive clearcoats, the real‐time evolution of the rheological properties of clearcoat resins during the crosslinking process with newly synthesized TRI derivatives was measured, confirming the different crosslinking kinetics of TRI derivatives in real thermal curing process. The results were found to be well correlated with data from the radical polymerization experiments of TRIs. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 3593–3600. Abstract : The new thermal radical initiators (TRIs) with linear and cyclic type groups based on derivatives of O ‐imino‐isourea have been designed and synthesized. The radical polymerization property and efficiency of the synthesized TRI derivatives as a radical initiator in n ‐butyl acrylate was monitored. It is noteworthy that the TRI derivatives with linear type groups show similar curing temperatures, whereas those with cyclic type groups could effectively reduce the curing temperature.